2002
DOI: 10.1128/jvi.76.17.8548-8550.2002
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Simian Varicella Virus Infection in African Green Monkeys

Abstract: Simian varicella virus (SVV) infection. The four naturally exposed monkeys developed mild varicella 10 to 14 days later, and skin scrapings taken at the time of the rash contained SVV DNA. Analysis of multiple ganglia, liver, and lung tissues from the four naturally exposed monkeys sacrificed 6 to 8 weeks after resolution of the rash revealed SVV DNA in ganglia at multiple levels of the neuraxis but not in the lung or liver tissue of any of the four monkeys. This animal model provides an experimental system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…The authors developed a model of natural SVV infection in monkeys by exposing SVV-seronegative monkeys to other monkeys that had been inoculated intratracheally with SVV [181]. These naturally infected monkeys harbor latent SVV DNA in ganglionic neurons [182] at multiple levels of the neuraxis [181], and both clinical and subclinical reactivation of SVV were induced by immunosuppression and stress [183].…”
Section: Animal Models Of Varicella Zoster Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors developed a model of natural SVV infection in monkeys by exposing SVV-seronegative monkeys to other monkeys that had been inoculated intratracheally with SVV [181]. These naturally infected monkeys harbor latent SVV DNA in ganglionic neurons [182] at multiple levels of the neuraxis [181], and both clinical and subclinical reactivation of SVV were induced by immunosuppression and stress [183].…”
Section: Animal Models Of Varicella Zoster Virus Infectionmentioning
confidence: 99%
“…These naturally infected monkeys harbor latent SVV DNA in ganglionic neurons [182] at multiple levels of the neuraxis [181], and both clinical and subclinical reactivation of SVV were induced by immunosuppression and stress [183]. Subclinical reactivation of latent SVV also occurs after irradiation in rhesus monkeys [184].…”
Section: Animal Models Of Varicella Zoster Virus Infectionmentioning
confidence: 99%
“…Hemorrhagic necrosis, inflammation and eosinophilic intranuclear inclusions are detected in skin and visceral tissues [147]. SVV establishes latent infection in neurons of multiple ganglia [148] and reactivates under stress to cause zoster [145]. VZV and SVV glycoproteins share immunologic cross-reactivity as demonstrated by the protection of SVV-infected monkeys after VZV immunization [149].…”
Section: Development Of Animal Modelsmentioning
confidence: 99%
“…SVV-seronegative monkeys are exposed to other monkeys previously inoculated intratracheally with SVV [148]. Ten to 14 days later, monkeys exposed to intratracheally inoculated monkeys develop a mild rash, and detection of SVV DNA in skin scrapings of naturally infected monkeys confirms that SVV causes the rash.…”
Section: Development Of Animal Modelsmentioning
confidence: 99%
“…A naturally transmitted infection of SVV has been shown to result in a scenario in which viral DNA is detectable only in the ganglia after 2 months [14]. We recently showed that in such naturally infected monkeys, latent virus was located exclusively in neurons in the spinal ganglia [15].…”
mentioning
confidence: 98%